(untitled) (Window of Public Health Journal, 2026)
The wood processing or furniture industry is a growing industrial sector in Indonesia. The wood processing process produces dust, which can be inhaled by workers. This dust can cause lung function disorders and other respiratory diseases. This study aims to analyze factors related to lung function disorders in workers in the furniture industrial area of Manggala District, Makassar City. This study used a quantitative, cross-sectional design. The study population consisted of all workers in the furniture industrial area of Manggala District, Makassar City. The sampling technique used was total sampling, with a sample size of 35 people. Data analysis was performed using the Chi-Square test at a 95% confidence level (α = 0.05). The results showed no relationship between age and lung function disorders (p = 0.736). There was also no relationship between length of service and lung function disorders (p = 0.734) or between smoking habits and lung function disorders (p = 0.615). Conversely, there was a significant association between length of work and impaired lung function (p = 0.002), as well as the use of personal protective equipment (PPE) in the form of masks and impaired lung function (p = 0.002). Based on the results, it can be concluded that work duration and the use of PPE (masks) are factors associated with impaired lung function among furniture industry workers in Manggala District, Makassar City. Therefore, there is a need to improve compliance with PPE use and to monitor workplace exposure to wood dust. These efforts can help prevent impaired lung function in workers.